Intervensi melalui social media campaign dan panduan kantin sehat untuk meningkatkan perilaku makan sehat pada mahasiswa Departemen Teknik Mesin, Universitas Gadjah Mada - Meia Audinah; Ribia Tutstsintaiyn; Atiq Harkati; Zainab Zainab; Fahmi Baiquni; Yayi Suryo Prabandari (Journal of Community Empowerment for Health, 2019)
Social media campaign intervention program and healthy canteen kit is a strategy to increasing knowledge, attitudes, and modify the environment in order to achieve improved healthy eating behavior of students of the Universitas Gadjah Mada (UGM) Mechanical Engineering Department. This study measured preeliminary outcomes from social media campaign interventions and the healthy canteen kit conducted in form of knowledge, attitudes, acceptance, and adoption of the program. This study used quasi experiment with quantitative and qualitative approach. First, quantitative research used pre-post test questionnaire (n = 52) to find out the changes in knowledge and attitudes of the social media campaign program. Second, qualitative research used semi-structured interview methods (n = 9) to determine the response and adoption of social media campaign programs and healthy canteen guidelines. The social media intervention campaign was conducted in May - August 2018 through official account Line and Instagram of KM DTM. Making process of a healthy canteen guide was a collaboration prepared together with the stakeholder in April - August 2018. The results on social media campaign programs presented a differences in mean of knowledge score of healthy eating before and after intervention with a significance level of 0.03 (p < 0.05) and there were significant differences in healthy eating attitudes before and after intervention ( p < 0.05) with an average difference of 1.0. Qualitatively, the dietary social media campaign showed good acceptance. Acceptance of healthy canteen guidelines was considered good and can be applied in the UGM Mechanical Engineering Department. Measuring the results of a healthy diet quantitatively and qualitatively showed positive results. The acceptance and adoption of healthy canteen guidelines is considered good and can be applied.